TYPOLOGY OF TRANSLATION ERRORS IN PROFESSIONAL INTERPRETING - Nataliia V. Zinukova (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2021)
The article considers the problem of typology of errors in professional interpretating based on the analysis of approaches and their classifications. Minding the main parameters of target text assessment (the degree of preserving the main content of the original text, correctness of language units and external impression), there were identified typical mistakes, which can help the interpreter prevent future difficulties and choose the right translation strategy. Based on general scientific methods (analysis and synthesis, observing and abstracting – to substantiate the theoretical grounds to determine the quality criteria of the translated text); comparative and translation analysis methods which made possible to compare the original and target texts to identify typical translation errors, descriptive-analytical and comparative methods, according to which the material being analyzed is generalized, typical translation errors are described and analyzed to identify the ways to prevent them. Minding such important constraints in interpreting activity – one-time presentation and tough time restrictions, the interpreter needs to resolve the situation on the spot and quickly, using short-term translation strategies over the long-term strategies. While interpretating in such conditions the issues of correct grammar, normative language, style of the original text may recede into the background. The main goal of an interpreter is to achieve immediate communication. Errors in the final translation text, which has already been given to the client, can lead to negative consequences: from a fine to a loss of trust and termination of cooperation. But in addition to this important role, mistakes and their consideration in professional activities are also a great tool to improve and find the proper translation strategy. The problem of errors typology in professional interpreting is not new, but today it is considered debatable. Modern classifications of translation errors are based on the principle of equivalence and adequacy, where the error is considered the discrepancy between the original and the translation. Moreover, errors are related to the distortion of the content or violation of the rules and usage of the language of translation. Based on the analysis of approaches and classifications of translation errors, we distinguish the following ones in professional interpretating: errors of perception, understanding, expression and behavior. Perception errors can be the result of information saturation of the source text (numbers, dates, names, proper names, etc.), unusual speaker’s accent, fast speech, insufficient extralinguistic and background knowledge, incorrect distribution of resources of attention and concentration. Misunderstandings of the original text can be caused by incorrect semantics, memory problems, analysis of the original message, misunderstanding of grammatical or lexical phenomena, inaccurate understanding of the meanings of some words in the original or ignorance of the subject of the message, inefficient or insufficient preparation for translation. The current situation requires the interpreter to understand not only the superficial level of expression, but also to recognize the deep intentions of the participants in communication, to determine the general context that describes the circumstances, time, objects, and so on. Expression errors can be the result of insufficient knowledge of the target language, violation of the rules of the target language, incorrect distribution of attention in the process of decoding the translation records. Such errors can result in the loss of a number of message elements in the target language as well. Behavioral errors can be caused by anxiety, excessive anxiety, inability to overcome stress and focus on the translation process, lack of experience in public speaking, and so on. Confident interpreter should have a good idea of the translation strategy, make and justify his translation decision. The first step is to determine the specifics of the picture of the world in two languages and cultures that are directly related to a particular unit of translation and that are relevant to the translation. Then the stylistics and structural features of languages should be taken into account. The second step consists of choosing a translation strategy that corresponds to the first step. This choice is made depending on the level of the translation unit. In case when the unit of translation belongs to the level of phrases, words and morphemes, transformations of concretization or generalization are used. The third step (tactics) involves the establishment of formal grammatical and structural relationships based on general logical operations: omission / addition, replacement / substitutions of semantic (and formal) components. ISSN 2523-4463 (print) ВІСНИК УНІВЕРСИТЕТУ ІМЕНІ АЛЬФРЕДА НОБЕЛЯ. ISSN 2523-4749 (online) Серія «ФІЛОЛОГІЧНІ НАУКИ». 2021. № 2 (22) It is established that the success of each situation of professional interpretating activity depends directly on the ability of an interpreter to choose the right translation decision, as a result of which the native speaker of the target language will react to the proposed text in such a way, which corresponds to the sender of the original text.